Plane orbits in the external gravitational field of precessing homogeneous ellipsoid - A. A. Tereshchenko (Вісник Астрономічної школи, 2009)
It is possible to find out such orbits that lie completely at some planes in the neighborhood of precessing homogeneous ellipsoid. Orientations of these planes depend both on the ellipsoid's triaxiality, rotation velocity, angle of precession, and eccentricity of the orbit. The conditions of stability of orbital plane's position relative to rotating coordinate system are obtained.